2019
DOI: 10.1111/jfpp.14346
|View full text |Cite
|
Sign up to set email alerts
|

Survival and stability of free and encapsulated probiotic bacteria under simulated gastrointestinal conditions and in pasteurized grape juice

Abstract: The present study was designed to explicate the effect of encapsulation on the stability of Bifidobacterium bifidum in pasteurized grape juice and in vitro gastrointestinal conditions. Purposely, hydrogel beads were prepared using sodium alginate and K‐carrageenan by internal gelation method. Free and encapsulated probiotics were incorporated in pasteurized grape juice samples. The initial count in grape juice samples with free probiotic cells was calculated as 9.35 log cfu/mL that reduced to 6.58 log cfu/mL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
(36 reference statements)
3
20
0
Order By: Relevance
“…The C2 (Sodium Alginate), C3 (Soy Protein Isolate), and C4 (Encapsulated with Sodium Alginate–Soy Protein Isolate)cells showed a gentle log reduction in comparison with nonencapsulated probiotics as showed in Table 8. Current study results are in line with the findings of Afzaal, Khan, et al (2019), Afzaal, Saeed, Arshad, et al (2019), Afzaal, Saeed, Saeed, et al (2019) who stated that encapsulation of cells with alginate enhanced the viability of probiotic in GIT environment. The results are also in line with Shi et al (2013) who observed that encapsulation could improve the stability of probiotic bacteria in simulated gastrointestinal conditions.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The C2 (Sodium Alginate), C3 (Soy Protein Isolate), and C4 (Encapsulated with Sodium Alginate–Soy Protein Isolate)cells showed a gentle log reduction in comparison with nonencapsulated probiotics as showed in Table 8. Current study results are in line with the findings of Afzaal, Khan, et al (2019), Afzaal, Saeed, Arshad, et al (2019), Afzaal, Saeed, Saeed, et al (2019) who stated that encapsulation of cells with alginate enhanced the viability of probiotic in GIT environment. The results are also in line with Shi et al (2013) who observed that encapsulation could improve the stability of probiotic bacteria in simulated gastrointestinal conditions.…”
Section: Resultssupporting
confidence: 92%
“…The encapsulation efficiency (EE %) expresses the efficiency of entrapped and survival of viable cells during microencapsulation procedure. The EE (%) was determined by digestion method as described by Afzaal, Khan, et al (2019), Afzaal, Saeed, Arshad, et al (2019), Afzaal, Saeed, Saeed, et al (2019) with slight modifications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, total soluble solids of L. acidophilus-tamarind juice were reduced over 21 days of cold storage (Figure 2c). Similar results were reported by Mokhtari et al (2019) and Afzaal et al (2020) where total soluble solids of probiotic-fruit juice reduced over storage at 4 °C. Both studies explained that the reduction of total soluble solids was due to the utilization of sugar by probiotic during storage.…”
Section: Physicochemical Properties Of L Acidophilus La-14 Tamarind Juice With or Without Beta-glucans During Cold Storagesupporting
confidence: 91%
“…To elicit the full effect in the host, the probiotic candidate microorganism should survive the harsh conditions encountered in the upper part of the digestive tract 59,60 Most of the bacteria isolated from food samples are very sensitive to the acidic conditions of the stomach, nevertheless, several members of LAB are acid-tolerant and can grow well in acidic conditions because of the presence of proton extrusion mechanism 61 . Protection of potential probiotic bacterium by the food matrix i.e.…”
Section: Survival Studies During Oro-gastric-intestinal Transitmentioning
confidence: 99%